FETISISME YANG DIALAMI OLEH TOKOH HACHIBE DALAM MANGA AI KORA KARYA INOUE KAZUROU - Ana Yuliani, Ni Kadek (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This research aims at fetishism of psychosexual about a figure named Hachibe in the Japanese novel taken from Inoue Kazurou. The result of data analysis was then presented with informal method. The theories used in this research are psychoanalytic theory taken from Sigmund Freud , semiotics taken from Marcel Danesi , drawing a comic theory taken from McCloud. According to the result of the analysis, the form of fetishism by Hachibe in the comic are straight foot like Sunny chan’s foot, blue safire eyes like a cat eyes, big breast like railway coach of Shinkansen type 200, bumpy of waist like Bizen’s porcelain, buttocks like peach, soft and length nape of neck, soft ears like a marsmallow, and sexy lip. Factor that caused fetishism such as the past life experience, imagination about sensuality fetish, and to appreciate and search fetish if to meet a woman in first time. The effort of Hachibe to overcome the fetishism are to be aware of self from mind about fetish and to throw all photos and collection about fetish. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Literary of Psychology, Psychoanalytic, Fetishism